Maternal iron status during pregnancy and attention deficit/hyperactivity disorder symptoms in 7-year-old children: a prospective cohort study - Andrés Díaz-López; Josefa Canals Sans; Jordi Julvez; Silvia Fernandez-Bares; Sabrina Llop; Marisa Rebagliato; Nerea Lertxundi; Loreto Santa-Marina; Mònica Guxens; Jordi Sunyer; Victoria Arija (Scientific Reports, 2022)
Abstract Evidence suggests that iron status may be linked to symptoms of childhood attention deficit/hyperactivity disorder (ADHD), but there is little data available on the relationship between iron status in pregnancy and the risk of developing ADHD. And the data that does exist is inconsistent. Our aim here is to assess the effect of maternal serum ferritin (SF) and haemoglobin (Hb) levels during pregnancy on manifestations of ADHD in children at 7 years of age. This prospective study analysed data from 1204 mother–child pairs from three Spanish cohorts participating in the INMA project. Maternal SF and Hb levels during pregnancy and other mother and child characteristics were collected. The children’s ADHD behaviours were reported by their parents using Conners’ Parent Rating Scale-Revised Short Form (CPRS-R:S). In the unadjusted regression analysis, maternal SF was positively associated with children’s T-scores on the subscales Cognitive problems/Inattention (β: 0.63, 95%CI 0.06–1.19; p = 0.029) and ADHD index (β: 0.72, 95%CI 0.20–1.24; p = 0.007). These associations were not present after multivariate adjustment or stratification by first and second trimester of pregnancy. The Hb levels were not related to any of the CPRS-R:S subscales in unadjusted or multivariate-adjusted models. We observed no association between maternal SF or Hb levels and the risk of ADHD symptomatology (T-score ≥ 65 for CPRS-R:S subscales). Our results suggest that neither maternal SF nor Hb levels during pregnancy are related to ADHD symptoms in 7-year-old children.